ADVANCES AND PERSPECTIVES OF CLINICAL ABZYMOLOGY - S. V. Suchkov; Z. S. Alekberova; A. N. Hitrov; Z. S. Shogenov; O. V. Voskresenskaya; N. V. Gnuchev; A. G. Gabibov (Медицинская иммунология)
Abstract. Natural catalytic autoantibodies (abzymes) posessing proteolytic (protoabzymes) and DNA-hydrolysing (DNA-abzymes) activities are detectable in clinical and experimental autoimmune disorders. Catalytic activity of abzymes is revealed in the patients with different forms of systemic (nonspecific) and organ-specific autoimmune pathology. The opportunity of assaying the abzymes for intensity monitoring of autoimmune disease is also described.